2008
DOI: 10.3748/wjg.14.7112
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of nestin in pancreatic tissue of mice at different ages

Abstract: We report for the first time the immunolocalization of NPC in the pancreas of mice of different ages (3 d to 8 wk) with reference to insulin and glucagon positive cells. The heterogeneous localization of the NPC observed may be of functional and developmental significance and suggest(s) that mice pancreatic tissue can be a potential source of progenitor cells. NPC from the pancreas can be isolated, proliferated and programmed to differentiate into insulin secreting cells under the appropriate microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Here, we found that GLP1R KD ΔNestin are highly resistant to the food intake and body weight lowering effects of liraglutide, supporting an important role for CNS GLP1R in mediating these effects. It should be noted that Cre driven by the nestin promoter has been widely used for loss-of-function of specific genes in the CNS, but it is expressed in other tissues, as evidenced by the reduced GLP1R in the pancreas of GLP1R KD ΔNestin animals (11,12). However, it is unlikely that other tissues targeted by nestin are likely to make large contributions to the effects of GLP1 analogs on these behavioral end points.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that GLP1R KD ΔNestin are highly resistant to the food intake and body weight lowering effects of liraglutide, supporting an important role for CNS GLP1R in mediating these effects. It should be noted that Cre driven by the nestin promoter has been widely used for loss-of-function of specific genes in the CNS, but it is expressed in other tissues, as evidenced by the reduced GLP1R in the pancreas of GLP1R KD ΔNestin animals (11,12). However, it is unlikely that other tissues targeted by nestin are likely to make large contributions to the effects of GLP1 analogs on these behavioral end points.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis was carried out using the primary polyclonal antiserum (Goat polyclonal anti Cox-2, 1:250, Santa Cruz, USA), and secondary antibody (FITC labeled Donkey anti goat - 1:500, Molecular probes, U.S.A) [17]. Images were captured on Nikon Eclipse microscope (TE 2000-S series) and the fluorescence intensity units (FIU) were corrected using appropriate controls (Primary antibody controls).…”
Section: Methodsmentioning
confidence: 99%
“…Homeostasis model of assessment for insulin resistance (HOMA-IR) was calculated using the following formula: Histology In order to perform the pancreatic histopathological study, pancreas were dissected, and processed for hematoxylene and eosin (H&E), Masson's trichome, immunohistochemistry and immune fluorescence using the standard immunohistochemistry protocols. 53 Briefly, formalin fixed, paraffin embedded sections of pancreas were mounted on poly-L lysine coated slides. Sections were dewaxed in xylene and rehydrated through graded ethanol.…”
Section: Plasma and Tissue Insulinmentioning
confidence: 99%